2005
DOI: 10.1007/s00497-004-0238-4
|View full text |Cite
|
Sign up to set email alerts
|

cDNA microarray analysis of gene expression changes during pollination, pollen-tube elongation, fertilization, and early embryogenesis in rice pistils

Abstract: During the processes of pollen recognition, pollen-tube guidance, fertilization, and early embryogenesis, a complicated gene network is highly regulated in plants. To visualize the profile of gene expression during these processes, we performed cDNA microarray analysis with RNA isolated from rice pistils at several stages. We identified 32 cDNA clones, in 21 nonredundant groups, with pistil-specific expression patterns. These genes could be clustered into five groups based on expression patterns, and included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In remodeling of the cell wall in the tip region, a nonspecific esterase/lipase is secreted into the extracellular medium and functions in the process of wall softening (Yoshida et al, 2005); its down-regulation indicated decreased activity in the continuous process of cell wall softening and a consequent increase in cell wall rigidity. Our proteomic data further confirm that the cell wall of gymnosperm pollen tubes undergoes dramatic remodeling during the perturbation of Ca 2+ -CaM signaling.…”
Section: Proteins Involved In Polysaccharide Synthesis As the Tertiarmentioning
confidence: 99%
“…In remodeling of the cell wall in the tip region, a nonspecific esterase/lipase is secreted into the extracellular medium and functions in the process of wall softening (Yoshida et al, 2005); its down-regulation indicated decreased activity in the continuous process of cell wall softening and a consequent increase in cell wall rigidity. Our proteomic data further confirm that the cell wall of gymnosperm pollen tubes undergoes dramatic remodeling during the perturbation of Ca 2+ -CaM signaling.…”
Section: Proteins Involved In Polysaccharide Synthesis As the Tertiarmentioning
confidence: 99%
“…The gene corresponding to clone TOBS008H02 encodes a ferredoxin 3 homolog and is specifically expressed at the reproductive organs, with a high expression level in ovaries. Interestingly, Yoshida et al (2005) also identified a rice pistil-specific gene encoding a ferredoxin III (Os3736; AC092557). Ferredoxins act as electron carriers in photosynthesis and play an important role in electron transfer processes.…”
Section: Real-time Rt-pcr Experiments and Validation Of The Macroarramentioning
confidence: 99%
“…Ferredoxins act as electron carriers in photosynthesis and play an important role in electron transfer processes. The pistil is a photosynthetic organ, and the elevation of ferredoxin transcript levels in pistils might be related to active electron transport in this organ (Yoshida et al, 2005) or involved in providing reductive agents to some specific metabolic process taking place in the reproductive organs.…”
Section: Real-time Rt-pcr Experiments and Validation Of The Macroarramentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional profiles of pollen (Becker et al, 2003;Twell, 2003, 2004;Pina et al, 2005; for review, see Becker and Feijó , 2007), embryo sac (Yu et al, 2005;Johnston et al, 2007;Jones-Rhoades et al, 2007;Steffen et al, 2007), pistil (Scutt et al, 2003;Tung et al, 2005), and embryo or seed developmental stages (Chen et al, 2001;Hennig et al, 2004;Yoshida et al, 2005, Le et al, 2010 were recently analyzed. More notably, recent progress in the isolation of Arabidopsis (Arabidopsis thaliana) gametes allowed genomewide expression profiling of purified sperm cells (Borges et al, 2008) as well as of isolated egg and central cells (Wuest et al, 2010).…”
mentioning
confidence: 99%